CITRA PERUSAHAAN SEBAGAI VARIABEL PEMODERASI PENGARUH LAYANAN TERHADAP KEPUASAN PASIEN DAN NIAT BERALIH - Muhammad Zakiy (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
This study aims to see the effect of service quality from 3 PKU Muhammadiyah Hospital in Jogja, Sleman and Bantul on customer satisfaction and customer switching intention which is moderated by the company's image. This study uses Moderated Regression Analysis (MRA), with a total sample of 111 customers/patients at the Muhammadiyah Yogyakarta Hospital. The data was collected online and offline by purposive sampling technique. This study proves that service quality is the main predictor in increasing customer satisfaction of PKU Muhammadiyah Yogyakarta hospital. However, the test results explain that the company's image is not able to moderate the influence of service quality on the customer satisfaction and switching intention. The results of this study also provide theoretical and practical contributions related to theoretical, methodological and practical issues.